Living and fossil Steginoporellidae (Bryozoa: Cheilostomata) from New Zealand - Gordon, Dennis P.; Voje, Kjetil L.; Taylor, Paul D. (Zootaxa, 2017)
The cheilostome bryozoan family Steginoporellidae in New Zealand comprises seven living species of Steginoporella. Three of these are new to science—Steginoporella discors n. sp., Steginoporella lineata n. sp. and Steginoporella modesta n. sp.—and one (Steginoporella magnifica) additionally occurs as a Plio-Pleistocene fossil. A new Early Pleistocene fossil species, Steginoporella tiara n. sp., is also recognised. The living species exhibit the full range of colonial morphologies known for the genus, and two of the new deep-shelf taxa described herein have the smallest known colonies, both linear, not exceeding 5 mm in width and 22 mm in length. One species has a recorded depth range down to 615 m, apparently the deepest known for the genus. Zooidal proportions vary, with a length:width ratio in the seven living species ranging from 1.31 to 1.81, exceeded only by that in the new fossil taxon, which has very elongate zooids. Notwithstanding the conspicuous differences in colonial and zooidal morphology, four of the living species appear to be closely related, sharing distinctive reticulation of opercular sclerites, a similar morphology of the median process and no B-zooid morphs. Only one New Zealand taxon has B-zooids. Biogeographically, all the species except S. magnifica (also known from Tonga) are nominally endemic, but it is possible that some of the deeper-water taxa may eventually be found outside the boundary of the New Zealand Exclusive Economic Zone. The operculum in Steginoporella species is initially a single thin layer continuous with the membranous frontal wall, becoming two-layered when fully functioning in feeding zooids and mandibulate B-zooids.